Serum alanine aminotransferase flares in chronic hepatitis B infection: the good and the bad. (April 2020) - Ghany, Marc G; Feld, Jordan J; Chang, Kyong-Mi; Chan, Henry L Y; Lok, Anna S F; Visvanathan, Kumar; Janssen, Harry L A
Summary: Chronic hepatitis B virus (HBV) infection follows a dynamic and variable course. At different stages in the disease, hepatitis flares might occur, which can be challenging to predict and manage. Flares are believed to be primarily immune-mediated and might mark transitions to inactive disease or clearance of infection, but in certain scenarios they might also lead to hepatic decompensation or death. As such, understanding of the clinical significance of flares in different patient populations and different scenarios is important for optimal management. In this Review, we summarise what is known about flares in different stages of chronic HBV infection; describe flares in the context of the natural history of chronic infection; summarise the immunological mechanisms underlying flares, and describe flares in different clinical scenarios. Each section reviews existing knowledge and highlights key unanswered questions that need to be addressed to improve the understanding of flares, hopefully providing insights into their pathogenesis that can be used to improve current clinical management and ideally to further develop new curative therapeutic approaches for HBV infection. We also propose a working definition of an ALT flare to facilitate future research.